Interactive Communication in Online Stores’ Marketing Strategy : A Content Analysis of an Algerian Online Store’s Instagram page (Vintage Stuff Only/ Thrift Lover) During the period from October 1st, 2023 to April 30th, 2024 - Ameur, Sara; Ghediri, Karima (École Nationale Supérieure de Journalisme et des Sciences de l'Information, 2024)
Our research project investigates the transformation of interactive marketing techniaues within the contemporary digital sphere. It examines the methods and technologies that companies employ to interact with consumers in a more engaging manner. The background of this research includes six former studies with their respective findings, which were vital to the foundation of our research, where the main purpose is to understand interactive communications and how they can be employed in the marketing strategy of brands, mainly within the realm of social media. Our analysis also encompasses a thorough review of existing literature, with the methodology of the research being qualitative and quantitative content analysis of an Algerian online store's instagram platforms in order to further our understanding of interactive marketing, offering insights into successful marketing practices and emerging consumer behavior patterns. By assessing both empirical data and theoretical models, this research's findings provide a comprehensive understanding of how interactive marketing techniques are employed in social media marketing, by assessing the most used post formats, content themes, and their respective interactivity rates.
103 f. : ill ; 12 cm.
Keywords: Communication en marketing; Marketing stratégique